Analisis Agroekologi dan Kebutuhan Irigasi Suplemen Untuk Tanaman Kakao di Provinsi Lampung - Bariot Hafif (Pusat Penelitian dan Pengembangan Perkebunan, 2017)
One of the factors that affect the productivity of cacao plants is water availability. Water deficit will negatively affect the development of cacao flowers and beans. Water stress is reported as one of the causes of low productivity on plantation crops in Lampung Province. The study was aimed to analyze the characteristics of agroecology and supplemental irrigation required for growth and production of cacao in Lampung. The research was carried out in the District of Pesawaran, Tanggamus, East Lampung, and South Lampung, Lampung Province, from 2012 to 2015. The study was conducted with the survey method and literature study for the collection of the primary and secondary data, related to the characteristics of the land agroecology. Geographically, the main cacao growing areas in this region is divided into two regions, western region consist of Pesawaran and Tanggamus District and east region comprise of East Lampung and South Lampung District. Based on agroecological zones, the planting of cacao in both regions is in accordance with the recommendations of land use. However, land suitability analysis showed that some of the agroecological characteristics of land becomes a limiting factor for the growth and production of cacao, including soil pH < 5.5, low cations exchange capacity (CEC) (< 16 cmol(+)/kg), air humidity > 75%, and in some areas there is an erosion hazard. Another obstacle is the water deficit that occurs during 140 days within 1 year of cacao growth cycle that occurred in July until mid-November. There are two factors that can be applied to increase cacao productivity in Lampung province, i.e. (1) an improvement of cacao cultivation technology that can address the characteristics of agroecology as a limiting factor of growth, and (2) an application of a supplemental irrigation technology to avoid cacao from water stress. The requirement of supplemental irrigation is 340.5 mm in western region and 209.7 mm in eastern region of Lampung.